2016
DOI: 10.4236/jss.2016.412009
|View full text |Cite
|
Sign up to set email alerts
|

Support for Altruistic Behavior in Rats

Abstract: Evidence for altruistic behaviors in rats has been continually building over many years, with a large surge in the past 10 years. Many researchers have posited that rats have the cognitive capabilities to engage in these altruistic behaviors that were at one time only attributed to species that are more complex. The results of many of the studies on altruistic behaviors in rats show parallels with non-human primate studies suggesting that what has been observed in rats is indeed altruism as it has been defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…We used rats because they form social groups of various sizes [16] and show kin [17,18] and individual recognition [19,20]. Importantly for our study, rats show a high propensity to cooperate (reviewed in [21,22]). For example, rats prefer to work with a partner, even if they could achieve the same reward individually [23].…”
Section: Introductionmentioning
confidence: 99%
“…We used rats because they form social groups of various sizes [16] and show kin [17,18] and individual recognition [19,20]. Importantly for our study, rats show a high propensity to cooperate (reviewed in [21,22]). For example, rats prefer to work with a partner, even if they could achieve the same reward individually [23].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are studies that support the investigation of physiological and pathological aspects of empathy in laboratory rodents (for review see Wrighten and Hall, 2016 ). For example, in mice, there are clear signs of emotional contagion ( Langford et al, 2006 ; Guzmán et al, 2009 ; Bruchey et al, 2010 ; Jeon et al, 2010 ; Kim et al, 2012 ; Nowak et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the psychological basis of prosocial behaviour and its fundamental mechanisms remain unclear 58 . Interestingly, in recent years, it has been reported that rats also show prosocial behaviour 913 . Rats rescued others in various situations, they donated food, they groomed conspecifics, and they freed trapped conspecifics 9,12 .…”
Section: Introductionmentioning
confidence: 99%